Comment on Kittichet et al. (doi: 10.1111/odi.14905) - Efsun Somay; Erkan Topkan; Ugur Selek; Berrin Pehlivan (Oral Diseases, 2025)
Objective This narrative review critically assesses the clinical relevance of pharmacogenomics within dental genomics, distinguishing clinically actionable applications from emerging or investigational findings. Materials and methods A targeted literature review was conducted in PubMed/MEDLINE, Scopus and Embase for publications from January 2000 to March 2026. The search focused on gene-drug interactions involving medications commonly prescribed or clinically relevant in dental care, including analgesics, NSAIDs, antiplatelet agents, anticoagulants, antibiotics and local anaesthetics. Relevant guidelines, landmark studies and key reviews were also considered. Results Most genomic findings related to oral diseases provide biological insights but limited routine clinical utility. Conversely, selected pharmacogenomic determinants show clearer applicability. CYP2D6 variability is the most robust example, influencing codeine and tramadol efficacy and toxicity. CYP2C9 variants may affect NSAID safety, while CYP2C19, VKORC1 and CYP2C9 are relevant in patients receiving antiplatelet or anticoagulant therapy. Other determinants, including SCN9A, CYP3A4/5 and ABCB1, remain investigational. Drug-drug interactions and phenoconversion further influence real-world responses. Conclusion Pharmacogenomics currently represents the most actionable area of dental genomics. Current evidence supports selective, scenario-based integration, particularly in pain management, adverse drug reactions, polypharmacy and medically complex patients.